2007
DOI: 10.1038/sj.jp.7211659
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin prophylaxis or expectant treatment of patent ductus arteriosus in extremely low birth weight infants?

Abstract: Background: Indomethacin prophylaxis or expectant treatment are common strategies for the prevention or management of symptomatic patent ductus arteriosus (sPDA). Objective:To compare the clinical responses of extremely low birth weight (ELBW) infants to indomethacin prophylaxis with hat of other infants who were managed expectantly by being treated with indomethacin or surgically only after an sPDA was detected.Methods: Retrospective cohort investigation of 167 ELBW infants who received indomethacin prophylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…[1,5,6] However, some studies [7,8] showed that prophylactic pharmacologic or surgical closure of PDA in small premature infants produced only short-term benefi ts like a decrease in later symptomatic PDA or a reduction in the duration of oxygen dependence. In an observational study, [9] a longer duration of indomethacin exposure was associated with less white matter injury in infants Factors affecting successful closure of PDA in ELBW infants Original article delivered before 28 weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%
“…[1,5,6] However, some studies [7,8] showed that prophylactic pharmacologic or surgical closure of PDA in small premature infants produced only short-term benefi ts like a decrease in later symptomatic PDA or a reduction in the duration of oxygen dependence. In an observational study, [9] a longer duration of indomethacin exposure was associated with less white matter injury in infants Factors affecting successful closure of PDA in ELBW infants Original article delivered before 28 weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic administration of indomethacin [32,33] administered immediately after birth may inhibit ductal closure further, and is contraindicated, and conservative treatment [34] is indicated. If the pediatrician waits for several days before administering indomethacin, the ductus may recover from the inhibitory effect of in utero exposure to indomethacin and become responsive to the drug.…”
Section: Extrapolation Of the Results To The Clinical Situationmentioning
confidence: 99%
“…IVH was diagnosed on head ultrasounds and graded accordingly. 10 We compared baseline demographic and clinical variables between the prophylactic indomethacin and the expectant groups to detect differences in potential confounders at baseline. Baseline characteristics were those that were present prior to onset of prophylactic indomethacin or 24 hours of life, whichever was earlier.…”
Section: Methodsmentioning
confidence: 99%
“…A few small studies suggest that it may not affect ventilation and oxygen requirements or it may, in fact, increase these requirements. [10][11][12] We conducted this retrospective cohort study to systematically evaluate the effects of prophylactic indomethacin on short-term respiratory outcomes.…”
mentioning
confidence: 99%